2014
DOI: 10.1007/s00426-014-0602-4
|View full text |Cite
|
Sign up to set email alerts
|

Mood states influence cognitive control: the case of conflict adaptation

Abstract: Conflict adaptation can be measured by the "congruency sequence effect", denoting the reduction of congruency effects after incongruent trials (where response conflict occurs) relative to congruent trials (without response conflict). Recently, it has been reported that conflict adaptation is larger in negative mood than in positive mood (van Steenbergen et al., Psychological Science 21:1629-1634, 2010). We conducted two experiments further investigating this important finding. Two different interference paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 47 publications
7
39
0
7
Order By: Relevance
“…Relatedly, inhibition of a dominant response tendency can also trigger stimulus devaluation (Wessel, O'Doherty, Berkebeile, Lindemann, & Aron, 2014), which corroborates a tight relationship between the evaluative and cognitive control processes. Furthermore, studies have shown that affective stimuli can modulate conflict adaptation, providing further evidence for a functional role of affect for control (Kuhbandner & Zehetleitner, 2011;Schuch & Koch, 2015;Schuch, Zweerings, Hirsch, & Koch, 2017;van Steenbergen, Band, & Hommel, 2009 but see Dignath, Janczyk, & Eder, 2017;Yamaguchi & Nishimura, 2019, Exp. 2 & 3).…”
mentioning
confidence: 95%
“…Relatedly, inhibition of a dominant response tendency can also trigger stimulus devaluation (Wessel, O'Doherty, Berkebeile, Lindemann, & Aron, 2014), which corroborates a tight relationship between the evaluative and cognitive control processes. Furthermore, studies have shown that affective stimuli can modulate conflict adaptation, providing further evidence for a functional role of affect for control (Kuhbandner & Zehetleitner, 2011;Schuch & Koch, 2015;Schuch, Zweerings, Hirsch, & Koch, 2017;van Steenbergen, Band, & Hommel, 2009 but see Dignath, Janczyk, & Eder, 2017;Yamaguchi & Nishimura, 2019, Exp. 2 & 3).…”
mentioning
confidence: 95%
“…The first empirical evidence for this sequential modulation was reported by Gratton, Coles, and Donchin (1992). This pattern has proven robust across tasks and paradigms (see Egner, 2007, for a review), although the size of the effect can be manipulated by factors such as reward (van Steenbergen, Band, & Hommel, 2009) or mood states (Schuch & Koch, 2015;van Steenbergen, Band, & Hommel, 2010).…”
mentioning
confidence: 95%
“…1A). Based on previous behavioral (van Steenbergen et al 2010;Schuch and Koch 2014;Gendolla et al 2015;van Steenbergen 2015) and neuroimaging work (Eryilmaz et al 2011;van Steenbergen et al 2015;Borchardt et al 2017;Song et al 2017;Young et al 2017), we predicted that negative affective contexts would cause distinctive changes among functionally integrated brain-wide networks at rest, including the DMN, SN, FPCN, and possibly other limbic networks (e.g., centered on amygdala and insula), with particular temporal fluctuations and distinctive distribution as a function of the preceding events. This allowed us to investigate several key questions including: (1) whether negative affect episodes produce lingering changes in subsequent brain activity and connectivity at rest, (2) whether these neural changes are also sensitive to the cognitive demands of executive control tasks, and (3) whether performance in executive control tasks themselves is altered by negative affect.…”
Section: Introductionmentioning
confidence: 90%
“…Cognitive control is defined as the flexible regulation of behavior in the pursuit of internal goals (Egner 2007;Helfrich and Knight 2016), and commonly assessed by Stroop and Flanker tasks where responding to goal-relevant targets is tested in the presence of distracting information (Botvinick et al 2001;Schmidt et al 2015). Negative emotions have been shown to alter cognitive control in such tasks at both the behavioral (van Steenbergen et al 2010;Schuch et al 2012;Brown et al 2014;Schuch and Koch 2014) and neural levels (Egner et al 2008;Etkin et al 2011;Braem et al 2013;Brown et al 2014;Song et al 2017; see also van Steenbergen 2015 for a review). Here we built on previous work showing an impact of negative affective episodes on subsequent brain resting state (Eryilmaz et al 2011) and cognitive control performance (Schuch and Koch 2014;van Steenbergen et al 2015), by probing for modulations of intrinsic functional brain connectivity and dynamics at the whole brain level following both affective and cognitive challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation